2020
DOI: 10.1093/cid/ciaa552
|View full text |Cite
|
Sign up to set email alerts
|

The Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Epidemic in Zimbabwe: Quo Vadis?

Abstract: The trajectory and impact of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic in sub-Saharan Africa are unclear, but they are seemingly varied between different countries, with most reporting low numbers. We use the situation in Zimbabwe to build an argument that the epidemic is likely to be attenuated in some countries with similar socioeconomic and cultural structures. However, even an attenuated epidemic may overwhelm weak health systems, emphasizing the importance of prevention. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Mutations in this receptor are a likely pathway to evade antibody recognition, such as described in other viruses [ 40 , 41 ]. In all the genomes analyzed, 36 non-synonymous RBD mutations were identified and all these mutations had a low frequency (<0.01) in the genomes of six continents, which is consistent with several studies that have found that mutations are extremely rare in the RBD region [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 42 , 43 ]. The calculated binding-free energy of mutant RBDs of spike protein complexed with human ACE2 revealed only four RBD mutant types (D364Y, N440K, N450K, S477R) displaying a much lower binding-free energy (ΔG), indicating a significantly higher affinity for the ACE2, which could influence the pathogenicity of SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Mutations in this receptor are a likely pathway to evade antibody recognition, such as described in other viruses [ 40 , 41 ]. In all the genomes analyzed, 36 non-synonymous RBD mutations were identified and all these mutations had a low frequency (<0.01) in the genomes of six continents, which is consistent with several studies that have found that mutations are extremely rare in the RBD region [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 42 , 43 ]. The calculated binding-free energy of mutant RBDs of spike protein complexed with human ACE2 revealed only four RBD mutant types (D364Y, N440K, N450K, S477R) displaying a much lower binding-free energy (ΔG), indicating a significantly higher affinity for the ACE2, which could influence the pathogenicity of SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, the dynamics of transmission showed that the least divergent African variants were grouped with Asian strains, while the most divergent were grouped with Europe and North America. This distribution points to different sources of infection [ 26 , 27 ]. South America’s genomes appear to originate from North America and Europe, showing a close clustering with Europe in low and high divergence strains, which is concordant with a previous study [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Status Quo of COVID-19 in Zimbabwe Despite the protracted socioeconomic challenges driven by inter alia bad governance amid unfavorable climatic factors such as recurring droughts and cyclones (Makuyana et al 2020), Zimbabwe has continued to be vigilant and proactive in trying to prevent and mitigate against the impacts of COVID-19 (Dziva 2020;Katsidzira et al 2020;Price 2020). Available statistics show that as of September 2020, Zimbabwe had recorded a total of 7,429 confirmed COVID-19 cases, 222 fatalities, and 5,542 recoveries (Ministry of Health and Child Care 2020).…”
Section: 1mentioning
confidence: 99%
“…Upon the confirmation of the first COVID-19 case in Zimbabwe, President Emmerson Mnangagwa on March 27, 2020 declared a state of disaster in respect of the pandemic (Price 2020). The President's declaration was accompanied by a raft of measures including the pronouncement of a mandatory 21 days (later extended by another 14 days and thereafter indefinite) national lockdown designed to prevent, slow, suffocate, and eventually thwart the spread of the pandemic (Katsidzira et al 2020;Price 2020). In synch with the President's declaration, the government, through the Ministry of Health and Child Care, promulgated Statutory Instruments (SI) 2020-077 Public Health (COVID-19 Prevention, Containment and Treatment) Regulations and SI 2020-110 Public Health (COVID-19 Prevention, Containment and Treatment) (National Lockdown) (Amendment) Order, 2020 (No.…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation